The impact on brand product sales of transitions from traditional to digital marketing solutions - Sekati, Moseki (University of the Witwatersrand, Johannesburg, 2023)
A lot of FMCG companies have been investing money in marketing activities with the aim of improving their business sales turnover, and this has been seen in both traditional marketing and digital marketing. However, literature show that there has been lack of knowledge on which strategy, digital or traditional, to invest in and what their benefits are. This study serves to address the identified research gap with regards to FMCG companies in South Africa. The main objective of this study is to investigate the positive effect of investment, implementation and understanding of digital marketing on financial performance. This study engages a quantitative research approach and collection of data through a research questionnaire that was constructed to answer the research questions. A causal design with a purposive sampling technique was used to collect data from a sample size 100 participants. The data was analysed using SPSS. The research findings had 4 out of 5 the hypotheses that were found to be significant, and another 6 th additional hypothesis that was computed. These hypotheses proved that investment in digital marketing; implementation and utilization of digital marketing have a positive impact on financial performance; and utilization of traditional marketing has a positive impact on financial performance. The 6 th computed hypothesis test showed that financial performance has an impact on preference for digital marketing. Companies in the FMCG and students in marketing can benefit from the finding of this study. This study makes recommendations for future research for understanding or knowledge of digital marketing, and what other important operations are a benefit of digital marketing
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2023
Keywords: Digital marketing; Traditional marketing; Media; Financial performance; FMCG; SDG-8: Decent work and economic growth